Silver Diamine Fluoride - Osadolor, Obehi O.; Osadolor, Aisosa .J. (Nepal Mediciti Medical Journal, 2023)
BACKGROUND Silver diamine fluoride can be used as an intervention or treatment for active and progressing untreated carious lesion not involving the pulp among children in slums, remote areas, rural areas and other underserved and un-served communities. Silver diamine fluoride stains teeth after use and it is available in different concentrations like 10 % , 12%, 30% and 38%. METHOD An electronic literature search in African journals online and Science direct was done in September , 2023 using the Population, Concept and Context framework. Search terms and keywords were combined by Boolean operators. Two independent investigators screened titles and abstracts of publications on silver diamine fluoride use among children. Original (primary) research articles with accessible full text were included for review, while review articles, systematic reviews, viewpoints, books, letters, thesis, editorials, book chapters, dissertations, perspectives were among articles excluded during screening. Original research articles involving teeth (in-vitro studies) were also excluded during screening. RESULTS Abstract and full texts were screened using inclusion criteria by two independent investigators. One article with accessible full text was included as it was assessed to meet the inclusion criteria and aim of the review. The study design was a randomised controlled clinical trial and it was carried out in Egypt. CONCLUSION Silver diamine fluoride (SDF) is a simple, non-aerosol-generating, painless, non-technique sensitive treatment procedure for active carious lesion not involving the pulp. More studies from diverse ethnic population in Africa countries will fill the gaps in knowledge and add to the existing literature.